Identification of Circular RNAs Related to Vascular Endothelial Proliferation, Migration, and Angiogenesis After Spinal Cord Injury Using Microarray Analysis in Female Mice - Ye, Xin; Chen, Yilei; Wang, Jiasheng; Chen, Jian; Yao, Ying; Wang, Lin-lin; Zhao, Fengdong (Frontiers in Neurology, 2021)
Background: Traumatic spinal cord injury (SCI) can result in severe disability and causes a considerable socio-economic burden worldwide. Circular RNAs (circRNAs) are important regulators of gene expression and pathological processes, and may represent therapeutic targets for SCI. To further evaluate the role of circRNAs in SCI, we elucidated circRNA expression profiles related to vascular endothelial proliferation, migration, and angiogenesis during the early stages of secondary injury in a mouse model of SCI. Methods: Microarray analysis was performed to investigate the circRNA expression patterns in the spinal cord 3 days after SCI in female mice. Bioinformatic analyses, including GO enrichment analysis, KEGG pathway analysis, and circRNA-miRNA-mRNA network construction, were conducted to explore the role of circRNA dysregulation in vascular endothelial proliferation, migration, and angiogenesis following SCI. Results: The expression of 1,288 circRNAs was altered (>2-fold change, p < 0.05) in the spinal cord after SCI, consisting of 991 upregulated and 297 downregulated circRNAs. We constructed a circRNA-mRNA network to predict whether these circRNAs could act as “miRNA sponges.” We next assessed the association of altered circRNAs with vascular endothelial proliferation, migration, and angiogenesis using GO and KEGG analyses. Using this analysis, we found that a total of 121 circRNAs were correlated with vascular endothelial proliferation, migration, and angiogenesis in the spinal cord after SCI. Conclusions: Our study provides circRNA expression profiles during the early stages of SCI. circRNA.7079, circRNA.7078, and circRNA.6777 were found to play key roles in the vascular endothelial proliferation, migration, and angiogenesis, and may represent therapeutic targets for SCI.